نمذجة ومحاكاة المبادل الحراري الحلزوني الصفائحي - ديبة, جابر سعيد; كرنو, علي محمد; يوسف, لينا إبراهيم (Latakia University Journal -Engineering Sciences Series, 2019)
في هذا البحث تم إعداد موديل رياضي لعمليات انتقال الحرارة وجريان الموائع ضمن المبادل الحراري الحلزوني الصفائحي وربط معادلاتها الواصفة مع الأبعاد التصميمية للمبادل ثم يتم إعداد نموذج برمجي باستخدام البرنامج الحاسوبي EES (برنامج حل المعادلات الرياضية الحرارية) حيث تم استخدام هذا النموذج لحساب وأمثلة كل من معامل انتقال الحرارة الإجمالي والاستطاعة الحرارية والمردود الحراري للمبادل وضياعات الضغط لكلا المائعين, ونتيجة لذلك تم إيجاد الحدود المثلى للأبعاد التصميمية للمبادل التي تحقق أعلى كفاءة. In this paper, a mathematical model has been made to the processes of the heat transfer and the liquids running into the plate spiral heat exchanger, and it has linked its describing equations with the designing dimensions of the exchanger. Then, a pragmatic model has been made by using the computer program EES (a program for the solution of the thermal mathematical equations). This model has been used to calculate and give examples to each of the total heating moving modulus, and the thermal ability, and the thermal output of the exchanger, and the pressure waste to both of the liquids. As a result, the idealistic boundaries of the designing dimensions of the exchanger which achieve the best competence have been found.